An evaluation strategy of state security level from the risk of external cyber influence - Бурячок, Володимир Леонідович; Корченко, Олександр Григорович; Хорошко, Володимир Олексійович; Кудінов, Вадим Анатолійович (Ukrainian Information Security Research Journal, 2013)
In industrialized countries, the task of protection level evaluation of its information and cyber infrastructure from the external cyber influence refers to the number of priority. The problem solving now is impossible without an integrated study of the systems cyber-security ability of these countries to counter such influence and its destructive effects. First of all it is caused by the continuous increase of the information, that circulates, accumulates and processed in the cyberspaces of these countries, and also by the increase of speed of its transmission, by the rapid development of new information and telecommunication technologies and general computerization, in particular, an access to the Internet, as well as the need to protect information from internal and external cyber threats and interferences. Taking the above mentioned into consideration, it was represented the strategy of actions which will give an opportunity: the first is to evaluate a level of state security from the risk of external cyber influence; the second is to obtain the quantitative value of " Cyber Power Index ", what characterizes the readiness of State objects cyberinfrastructure for safe operation under such conditions; thirdly, to establish requirements for the State systems development of cyber-security and to develop measures aimed to increase its effectiveness. It was established, that the level of cyber security awareness to attacks in cyberspace, mainly depends on the presence of implemented regulatory framework and the substantial technological infrastructure of the country, the condition of its socio-economic development, as well as the usage of information and communication technologies and systems by the country. For protection level evaluation it was offered to use the questionnaire method - one of the known methods of expert assessment.